Pelanggaran Etika dan Profesi Hukum Pada Kasus Suap Penegak Hukum - Pinasti, Putri; Kayowuan L, Kayus (Media Hukum Indonesia (MHI), 2025)
Ethical violations in the form of bribery among law enforcers (judges, prosecutors, police, and advocates) have become a systemic problem in Indonesia, undermining the principles of justice and public trust. This study aims to identify the forms of violations, driving factors, and strategies to eradicate bribery through a qualitative approach with a literature study method. The results show that ethical violations in the form of bribery/gratification, abuse of authority, conflict of interest, manipulation of evidence, and the role of intermediary advocates/clerks dominate cases such as bribery against Judge Ronald Tannur and gratification at the Juanda Airport Customs. The causal factors include weak individual integrity, materialistic work culture, ineffective supervision systems, weak legal sanctions, and political intervention. Proposed solutions include strengthening internal supervision, anti-corruption education from an early age, legal reform with strict sanctions, and protection for whistleblowers. This study emphasizes that eradicating bribery requires a holistic effort to restore the integrity of the legal profession and public trust.